Kuat Tekan Beton Serat Menggunakan Variasi Fibre Optic dan Pecahan Kaca - Sustika Pratiwi; Hakas Prayuda; Fadillawaty Prayuda (Universitas Muhammadiyah Yogyakarta, 2016)
Fibre concrete is one of special concretes which developed from normal concrete by adding fibre into concrete mortar. It aims at preventing crack of loading, heat hydrating as well as depreciation and to increase the stress force, bent force, and tensile force. In this research used the fibre optic which is a synthetic fibre obtained from the inside of optic cable. Glass is a material which is easy to find and has an economic value, beside that glass also has excellent resistance of abrasion, weather or chemical attack. This research uses three variations of fibre grade that are 0,1%; 0,15%; 0,2% with the length 10 cm obtained from concrete weight, while glass fracture that used is 20% of sand weight. Average Compressive strength of fibre addition consecutively 22,43 MPa; 24,31 MPa and 29,63 MPa. Compressive strength increased with the increasing number of fibre.